Numerical modelling of dynamic ductile fracture propagation in different lab-scale experiments using GTN damage model - Benoît Paermentier; Dimitri Debruyne; Reza Talemi (Fracture and Structural Integrity)
Initiation and propagation of ductile fractures are a major consideration during the design of high-pressure pipelines. Consequences of a pipeline failure can be catastrophic thus structural integrity must be ensured over several decades. Traditional lab-scale experiments such as the Charpy V-Notch (CVN) and Drop Weight Tear Test (DWTT), impact experiments on a notched three-point bending sample, are widely used to measure the fracture toughness of a material. However, with increasing wall thickness and the transition to high-grade steels in the pipeline industry, the size-effect of the specimen and inverse fracture became prominent issues. A new testing methodology called the Dynamic Tensile Tear Test (DT3) is currently investigated as to address the issues presented by the current state of the art.